Experimental Investigation on the Correlation between Dynamic Ultrasonic and Mechanical Properties of Sandstone Subjected to Uniaxial Compression - Yunjiang Sun; Jianping Zuo; Yue Shi; Zhengdai Li; Changning Mi; Jinhao Wen (Geofluids)
Ultrasonic wave velocity is effective to evaluate anisotropy property and predict rock failure. This paper investigates the correlation between dynamic ultrasonic and mechanical properties of sandstones with different buried depths subjected to uniaxial compression tests. The circumferential anisotropy and axial wave velocity of sandstone are obtained by means of ultrasonic wave velocity measurements. The mechanical properties, including Young’s modulus and uniaxial compressive strength, are positively correlated with the axial P wave velocity. The average angles between the sandstone failure plane and the minimum and maximum wave directions are 35.8° and 63.3°, respectively. The axial P wave velocity almost keeps constant, and the axial S wave velocity has a decreasing trend before the failure of rock specimen. In most rock samples under uniaxial compression, shear failure occurs in the middle and splitting appears near both sides. Additionally, the dynamic Young’s modulus and dynamic Poisson’s ratio during loading are obtained, and the negative values of the Poisson’s ratio occur at the initial compression stage. Distortion and rotation of micro/mesorock structures may be responsible for the negative Poisson’s ratio.